The Development of Transfusion-Related Acute Lung Injury for the Second Time: A New Awareness for Daratumumab?. (September 2021) - Turgutkaya, Atakan; Bolaman, Ali Zahit; Yavaşoğlu, İrfan
Transfusion-related acute lung injury (TRALI) is an undesired and potentially fatal complication of blood transfusion. Besides human neutrophil and leukocyte antigens of the donor blood; especially for red blood cell transfusions, nonantibody-mediated mechanisms seem responsible. Among these patients, pulmonary neutrophils have increased sensitivity to initiate TRALI. It is a very rare event for a patient to develop a second reaction. Comorbid conditions such as kidney failure and cardiovascular diseases may pose a risk. Daratumumab, an anti-CD38 monoclonal antibody, seems unrelated because it only causes indirect Coombs positivity without triggering transfusion complications. However, its role in recipient–donor interactions causing TRALI is less clear. Here, we report a relapsed multiple myeloma-diagnosed patient who developed TRALI under daratumumab treatment.